Beyond Compliance: A Systematic Review of Ethics, Accountability, And Transparency in Indonesian Governance - Rahmah Hanifa, Maftuh; Dwi Wahyunengseh, Rutiana; Suharto, Didik Gunawan; Gunawan Suharto, Didik (Policy & Governance Review, 2026)
This article discusses a Systematic Review of Ethics, Accountability, and Transpar- ency in Indonesian Governance. This topic falls within the public ethics and public accountability cluster in public administration studies, which emphasizes how moral principles, institutional integrity, and accountability mechanisms establish transparent and trustworthy governance. For a long time, accountability studies focused more on fiscal reporting and administrative control, while transparency focused on regulations and digitalization, and ethics related to corruption or the individual behaviour of of- ficials. However, there are significant lacks of research that systematically integrates these three aspects. This article fills that gap through a systematic literature review of publications from 2015 to 2025 regarding ethics, accountability, and transparency in the public sector in Indonesia. Based on the classic Friedrich-Finer debate, prin- cipal-agent theory, and the Public Accountability Framework, this analysis positions ethics as a normative foundation, transparency as an information tool, and account- ability as a multidimensional practice. The results show that despite digitization initia- tives, a weak ethical foundation hinders their effectiveness in preventing corruption and eroding public trust. This article synthesizes diverse literature and proposes an integrated public administration governance framework that emphasizes the impor- tance of ethical, accountable, and transparent governance in Indonesia, while also enriching the governance discourse.